Diagnosis Histopatologis Lymphoma Non-Hodgkin Disesuaikan Dengan Pengelolaan Penderita - Soeripto Soeripto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1990)
Rappaport non-Hodgkin lymphoma classification is well known, by pathologists and clinicians. This classification is based on the morphology of tumor cells. Lukes and Collins classification, and also Lennert classification are new non-Hodgkin lymphoma classifications. These classifications are based on morphology, basic function of tumor cells, and the clinical application. However, there are some differences between Rappaport classification, Lukes and Collins classification and Lennert classification. To compromise the differences of the classifications, there is a working classification of non-Hodgkin lymphoma which is used for clinical diagnosis.It is important to discuss the non-Hodgkin lymphoma classifications because each classification has its own basis. The basic classification of non-Hodgkin lymphoma is useful for the specialists based on their specialties; Lennert classification, and Lukes and Collins classification are the applicable classifications of non-Hodgkin lymphoma for pathologists and clinicians, while Rappaport classification is more useful for pathologists.Key Words: non-Hodgkin lymphoma histopathological diagnosis of lymphoma - basic function of tumor cells - leucaemia - Sezary's syndrome